2022
DOI: 10.1038/s41375-021-01502-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of combined inhibition of anti-apoptotic molecules in B-cell precursor ALL

Abstract: Targeting BCL-2, a key regulator of survival in B-cell malignancies including precursor B-cell acute lymphoblastic leukemia, has become a promising treatment strategy. However, given the redundancy of anti-apoptotic BCL-2 family proteins (BCL-2, BCL-XL, MCL-1), single targeting may not be sufficient. When analyzing the effects of BH3-mimetics selectively targeting BCL-XL and MCL-1 alone or in combination with the BCL-2 inhibitor venetoclax, heterogeneous sensitivity to either of these inhibitors was found in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…Thus, this drug combination may sensitize cells with both survival proteins overexpressed and overcome the resistance to both drugs individually. Consistent with our findings, a recent study of venetoclax and S63845 (an alternate MCL-1 inhibitor) in diploid leukemias demonstrated synergistic anti-leukemia activity through the impaired binding of BCL-2 and MCL-1 to the apoptosis activator BIM 32 . Thus, for hypodiploid B-ALL, which has elevated levels of both BCL-2 and MCL-1, as well as the proapoptotic proteins (BIM, BAD, and/or PUMA) this drug combination may represent a promising targeted therapeutic approach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, this drug combination may sensitize cells with both survival proteins overexpressed and overcome the resistance to both drugs individually. Consistent with our findings, a recent study of venetoclax and S63845 (an alternate MCL-1 inhibitor) in diploid leukemias demonstrated synergistic anti-leukemia activity through the impaired binding of BCL-2 and MCL-1 to the apoptosis activator BIM 32 . Thus, for hypodiploid B-ALL, which has elevated levels of both BCL-2 and MCL-1, as well as the proapoptotic proteins (BIM, BAD, and/or PUMA) this drug combination may represent a promising targeted therapeutic approach.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with our findings, a recent study of venetoclax and S63845 (an alternate MCL-1 inhibitor) in diploid leukemias demonstrated synergistic anti-leukemia activity through the impaired binding of BCL-2 and MCL-1 to the apoptosis activator BIM. 32 Thus, for hypodiploid B-ALL, which has elevated levels of both BCL-2 and MCL-1, as well as the proapoptotic proteins (BIM, BAD, and/or PUMA) this drug combination may represent a promising targeted therapeutic approach. Given the cytotoxic rather than cytostatic effect of both venetoclax and dinaciclib, this combination provides a strong rationale for a complementary and effective therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%
“…In concordance with our results demonstrating the selective senolytic effect on irradiated RPE-1 cells, a new study showing the selective senolytic effect of Venetoclax on radiotherapy-induced senescent sarcoma cell lines has been published [ 69 ], broadening the potential application range of Venetoclax. It should be noted that the combination of BCL-2 (Venetoclax) and MCL-1 (S63845) or BCL-XL (A-1331852) was effective against precursor B-cell acute lymphoblastic leukemia, as reported recently using patients' xenografts in mouse model [ 70 ].…”
Section: Discussionmentioning
confidence: 91%
“…Excitingly, idasanutlin in combination with chemotherapy or venetoclax is currently progressing to phase I/II clinical trials for relapsed pediatric AML and ALL patients (NCT04029688). However, unlike AML blasts which are predominantly BCL-2 dependent [ 42 ], ALL blasts often exhibit anti-apoptotic dependence on both BCL-2 and BCL-x L [ 43 45 ]; with exception to specific subtypes [ 44 , 46 , 47 ]. Accordingly, Khaw and colleagues showed venetoclax to be effective against only a minority of B-ALL xenografts in vivo, whereas combined BCL-2/BCL-x L inhibition resulted in synergistic killing in most models [ 47 ].…”
Section: Discussionmentioning
confidence: 99%